Pengembangan Aplikasi Peta Pariwisata Digital Menggunakan Metode Markerless Di Kota Palembang - Hidayat, Kemas Muhammad Wahyu (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Based on the results of data obtained from the Palembang city tourism office, activities providing information about tourism are not running optimally in reaching prospective domestic and foreign tourists because activities for conveying information about the attractiveness of tourist attractions through brochures, newspapers, and other print media, as well as events being held, are still ongoing. is temporary; in other words, the delivery of information has not become a routine activity by the Palembang City Culture and Tourism Office. Apart from that, the lack of information related to tourist attractions in Palembang can make it difficult for tourists to determine destinations and travel plans because descriptions of areas or tourist attractions, such as visualization of places and distances between one location and another, are unavailable. Therefore, tourists waste time looking for tourist attractions to visit. This research aims to develop a Digital Tourism Map application in Palembang City which is presented with Augmented Reality in the form of 3D Objects using the Markerless Method so that it can make it easier for local and outside tourists in the Palembang City Area to get to know the tourist attractions in Palembang City. One method currently being developed is the Markerless method; with this method, users no longer need to print a marker to display digital elements